Evaluation of hydrocarbons level and identification of indigenous bacteria in soil from auto-mechanic workshops along Ikokwu Mechanic Village, Port Harcourt, Nigeria - O.N. Akomah; A.D. Osayande (Journal of Applied Sciences and Environmental Management, 2018)
Soil samples collected from Ikokwu auto-mechanic village Mile 3, Port Harcourt, Nigeria were analyzed for the microbiological and hydrocarbon content using standard culture dependent and physiochemical methods. Five sets of soil designated A, B, C, D and E were collected using composite technique at depth 0 - 15 cm and 15 -30 cm. The parameters analyzed over an experimental period of 60 days were; total heterotrophic bacteria (THB), hydrocarbon utilizing bacteria (HUB), total petroleum hydrocarbon (TPH), polyaromatic hydrocarbon (PAH) and total hydrocarbon content (THC). The total heterotrophic bacterial count (THB) ranges from 1.36 x 106 - 1.10 x 108 cfu/g for A- E (0-15) cm and 5.0 x 105 - 7.0 x 107cfu/g for (15-30) cm while the total hydrocarbon utilizing bacteria (HUB) count ranges from 3.5 x 105 - 5.4 x 106cfu/g for (0-15)cm and 2.0 x 105 - 9.4 x 106 for (15-30) cm. The bacteria isolates included the genera Bacillus sp., Flavobacterius sp., Pseudomonas sp., Micrococcus sp., Arthrobacter sp., Acetobacter sp., Proteus sp. and Staphylcoccus sp. The TPH ranges from 34.32 - 1746.6mg/kg for (0-15) cm and 29.49 -1141.0 mg/kg for (15-30) cm. The THC ranges from 1.3 - 5.66 mg/kg for (0-15) cm and 0.84 - 2.719 mg/kg for (15-30) cm. PAH recorded a value of 3.246 - 6.890 mg/kg for (0-15) cm and 0.096 - 2.860 mg/kg for (15-30) cm. It is recommended that (i) the hydrocarbon degraders be enhance and employed for bioremediation of auto-mechanic workshop (ii) it is essential that the metagenomics of spent engine oil contaminated soil at auto-mechanic workshop be studied for optimum utilization of their potentials.